2021
DOI: 10.15252/emmm.201911814
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Discoidin Domain Receptors DDR1 and DDR2 overcomes matrix‐mediated tumor cell adaptation and tolerance to BRAF‐targeted therapy in melanoma

Abstract: Resistance to BRAF/MEK inhibitor therapy in BRAF V600 -mutated advanced melanoma remains a major obstacle that limits patient benefit. Microenvironment components including the extracellular matrix (ECM) can support tumor cell adaptation and tolerance to targeted therapy; however, the underlying mechanisms remain poorly understood. Here, we investigated the process of matrixmediated drug resistance (MMDR) in response to BRAF V600 pathway inhibition in melanoma. We demonstrate that physical and structural cues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 72 publications
2
30
0
Order By: Relevance
“…Usually, a trade-off average concentration has to be selected within the activity range of all small-molecule compounds used. This value is generally within the range of 1 -15 µM in most zebrafish in vivo pharmaceutical screens (Bowman and Zon, 2010;Colanesi et al, 2012;Haney et al, 2021;Oprisoreanu et al, 2021;Precazzini et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Usually, a trade-off average concentration has to be selected within the activity range of all small-molecule compounds used. This value is generally within the range of 1 -15 µM in most zebrafish in vivo pharmaceutical screens (Bowman and Zon, 2010;Colanesi et al, 2012;Haney et al, 2021;Oprisoreanu et al, 2021;Precazzini et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, we demonstrated that the inhibition of proteins related to cell cycle and migration can be useful in targeting leukemic expansion in vivo. Inhibitors targeting discoidin domain receptor 1 (DDR1), BAY-826 and DDR-IN-1 are promising hits as DDR1 inhibition has potential in cancer therapy (Berestjuk et al, 2022;Elkamhawy et al, 2021). Moreover, DDR1 therapeutic targeting in vivo was not yet characterized for the treatment of myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, DDR1 inhibition prevents EMT through the MKK7 and Pyk2 signaling pathways, which cause apoptosis in the prostate tumor cell. Accordingly, DDR1 activates EMT via stimulating the protein expression of N-cadherin and vimentin and phosphorylation of Pyk2 and MKK7 in prostate cancer [ 154 ].…”
Section: Biological Regulationmentioning
confidence: 99%